Regio‐ and Stereoselective Iron‐Catalyzed Oxyazidation of Enamides Using a Hypervalent Iodine Reagent. Issue 70 (30th November 2017) - Bertho, Sylvain; Rey‐Rodriguez, Romain; Colas, Cyril; Retailleau, Pascal; Gillaizeau, Isabelle
Abstract: A novel regio‐ and diastereoselective iron‐catalyzed intermolecular oxyazidation of enamides using various azidobenziodoxolone (ABX) derivatives is presented. A variety of α‐N3 amino derivatives and of α‐N3 piperidines were synthesized in good yields and under mild reaction conditions. The reaction involves a radical process using cheap FeCl2 as the initiator. Abstract : Iron catalysis : An iron‐catalyzed oxyazidation of enamides was developed. This provided an efficient route to α‐N3 amino derivatives and more specifically α‐N3 piperidine derivatives in good yields with high regio‐ and diastereoselectivity.